Detection Of Pork And Lard Adulteration In Food Products Using Molecular Biology Techniques For Halal Authentication - Azmi, Aida Azrina (2007)
Adulteration of food products has become a common problem in many countries. Adulteration may take the form of substitution of one species for another whereby the food products from one species have been mixed intentionally with either similar substitute material or cheaper species. In most cases, food manufacturers often choose lard as a substitute ingredient for oil because it is cheap and easily available. However, the usage of pork and lard is a serious matter in Islam because foods containing ingredients from pig sources are haram (unlawful or prohibited) for Muslims to consume. Therefore, a reliable technique for detection of pork and lard adulteration in food products is necessary in order to protect Muslim consumers from intentional or non- intentional fraud. Polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) techniques have been developed for species identification in various types of food products such as canned fish, peanut and milk. These techniques are proven to be rapid and specific in detecting species adulteration. In this study, rapid methods using PCR and ELISA were utilized to detect pork and lard adulteration in selected food products. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and species-specific PCR detection of the conserved region in the mitochondrial (mt) cytochrome (cyt) b gene and mt 12S rRNA gene, respectively, for species identification from raw meat, fat and three types of food products were optimized and developed. Genomic DNA of raw meats, fats and sausages were successfully extracted and were found to be of good quality. Genomic DNA was not detected from the extraction of casing samples and the yield of genomic DNA extracted from bread and biscuit samples were very low. PCR amplifications of mt cyt b gene and 12S rRNA gene produced DNA fragments of approximately 360 bp and 387 bp, respectively from the meat samples. However, no amplification product was observed from the bread and biscuit samples. The amplicons from the mt cyt b gene amplification were then digested with RE BsaJI resulting in species-specific RFLP profiles. The cyt b PCR-RFLP and species-specific PCR identification yielded excellent results for detection of pig derivatives in food products Crude protein were successfully extracted from three types of food products and subjected to ELISA. Using this technique, ten samples were shown to be contaminated with pig derivatives. Positive results were confirmed by observing the colour changes in the well of the ELISA plate. This technique highlighted an alternative in detection of pig derivatives in food products. From these studies, the utilization of PCR-RFLP and the utilization of mt cyt b and 12S rRNA gene in detecting pork and lard adulteration in selected food products were demonstrated. The use of ELISA was also shown to be fast and reliable in identification of pork and lard adulterated food products. However, PCR-RFLP and specific PCR techniques were determined to be better detection techniques for pork and lard adulteration in food products compared to ELISA. The findings from this study can serve as a basis of reference for the research in halal food authentication.